Dialectal variation in European Portuguese Central Vowel Perception - Horn, Valerie (2020)
The present paper aims at providing empirical evidence for dialectal variation concerning the perception of the central vowel [ɐ] in European Portuguese (EP). More concretely, this study compares the perception of the contrast between [a] and [ɐ] by native speakers of two varieties of EP: 23 speakers of a northern Portuguese dialect (from the city of Braga) and 23 speakers of the Littoral Center variety of EP (from the city of Lisbon, defined as Standard European Portuguese (SEP)). Based on a discrimination test, the results show that the two groups of speakers differ with respect to the perception of the contrast between the two central vowels under investigation. The speakers of the northern variety differentiate less between the two central vowels compared to the speakers from Lisbon.